Experimental Determination of Ferrocast Confined Cylindrical Columns (International Journal of Scientific Research and Management (IJSRM), 2017)
Methods of construction have changed over ages. As new materials of construction were evolved, new suitable techniques to exploit their use were developed. Similarly, use of ferrocast sections is a recently developed technique which is similar to precast sections. This experimental study analyses the behavior of column in bending as well as under axial compressive loading. This study included total 11 samples of confined columns and were tested for different types of loading cases. Interpretation of the results was carried based on the comparison between cubes without confinement and cylindrical sections with confinement. After comparison, increment in compressive strength was observed in confined sections and development of tensile stress was also observed